Kerentanan Perbankan di Indonesia - Amir Ambyah Zakaria; Wisnu Wibowo (Trunojoyo University of Madura, 2020)
This research aims to measure the banking vulnerability index and test the factors that influence the banking crisis. The crisis and variable identification that triggered the banking crisis is still a debate. This study uses banks in Indonesia which listed in JKSE for the period 2009 to 2014 as samples. This study uses index calculations as identification of possibility individual banking crisis, and examines bank internal variable, macroeconomic variable, and global economic variables that are thought to trigger the banking crisis using logit regression. The result is that bank internal factors proxy by non-performing loans, labor cost ratios and loans to deposits ratios have a positive relationship with the banking crisis, while net interest margins and interest income have a negative relationship with the banking crisis. Macroeconomic and global economic variables proxy by domestic inflation and US interest rates have a positive effect on the banking crisis while M2 growth, and GDP growth in the USA have a negative effect on the possibility of a banking crisis in Indonesia.